EFEKTIFITAS TEKNIK SERANGAN PENCAK SILAT PADA KEJUARAAN PEKAN OLAHRAGA PELAJAR DAERAH (POPDA) SE -KOTA PONTIANAK - Nuraisyah yarso; Edi Purnomo; Eka supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research was how much the effectiveness of pencak silat attack techniques at the POPDA Championship in Pontianak City. This research aimed to determine the effectiveness of the results of pencak silat attack techniques at the Regional Student Sports Week (POPDA) championship in the city of pontianak. The research used a survey method, with descriptive percentages. The population in this research were 32 party pencak silat matches at the Regional Student Sports Week Championship (POPDA) in all cities in Pontianak. The sample were all male and female athletes who managed to escape to the semifinals and finals in the championship of the Regional Student Sports Week (POPDA) throughout the city of pontianak. The results of the research showed that the effectiveness of attack techniques on Men's Games: 1. A punch attack technique with a percentage of 55%, 2. A kick attack technique with a percentage of 59%, 3. Falling attack technique with a percentage of 26%. Women's game: 1. Punch attack technique with a percentage of 83%, 2. Kick attack technique with a percentage of 54%, 3. Falling attack technique with a percentage of 27%. Then it can be concluded that in the POPDA (Regional Student Sports Week) match in the City of Pontianak that effective attack techniques on the men's match are 59% kick and female match with a percentage of 83%. Keywords : Attack technique, Effectiveness, Pencak Silat.